Evaluation Of Local Carbon Source In The Biofloc System For Juvenile Pangasius-Pangasius Culture Using Small-Scale Plastic Pond In Central Java, Indonesia - Sukardi, Purnama; Prayogo, Norman A.; Pramono, Taufik Budhi; Sudaryono, Agung; Harisman, Taufan (Aquacultura Indonesiana, 2019)
The aim of the study was to investigate the effect of different types of carbohydrates on growth, survival, feed efficiency and fish production (Pangasius pangasius), in the biofloc system with zero-water exchange. Added carbohydrates were tapioca, molasses, bran and cornstarch which were set at level of 25% of the theoretical adding quantity. A total of 6000 fish larvae used in this experiments. Complete Randomized Designed was used with four treatments and three replications. Twelve tanks used in which each tank was a cylinder tank (1814.92 L) and each tank contained 500 fish. The results showed that the concentrations of ammonia and nitrite differ significantly in the experimental tank added maize when compared to other carbohydrate sources. The nitrate levels showed that highly concentration was observed in the maize treatments compare to tapioca and molasses treatments, however it was not significantly different than that of rice bran treatments. The floc volume stabilized after about 3 weeks in the BFT tanks. Different carbon sources had resulted in different proximate composition tendencies. The highest yield obtained in molasses treatments which were highest compare to all carbohydrate treatments, whilst tapioca, rice bran, and maize treatments were not significantly different